Cephalopod‐Inspired High Dynamic Range Mechano‐Imaging in Polymeric Materials. (23rd July 2020) - Clough, Jess M.; van der Gucht, Jasper; Kodger, Thomas E.; Sprakel, Joris
Abstract: Cephalopods, such as squid, cuttlefish, and octopuses, use an array of responsive absorptive and photonic dermal structures to achieve rapid and reversible color changes for spectacular camouflage and signaling displays. Challenges remain in designing synthetic soft materials with similar multiple and dynamic responsivity for the development of optical sensors for the sensitive detection of mechanical stresses and strains. Here, a high dynamic range mechano‐imaging (HDR‐MI) polymeric material integrating physical and chemical mechanochromism is designed providing a continuous optical read‐out of strain upon mechanical deformation. By combining a colloidal photonic array with a mechanically responsive dye, the material architecture significantly improves the mechanochromic sensitivity, which is moreover readily tuned, and expands the range of detectable strains and stresses at both microscopic and nanoscopic length scales. This multi‐functional material is highlighted by creating detailed HDR mechanographs of membrane deformation and around defects using a low‐cost hyperspectral camera, which is found to be in excellent agreement with the results of finite element simulations. This multi‐scale approach to mechano‐sensing and ‐imaging provides a platform to develop mechanochromic composites with high sensitivity and high dynamic mechanical range. Abstract : A high dynamic range mechano‐imaging (HDR‐MI) polymeric material integrating physical and chemical mechanochromism produces HDR mechanographs, with an expanded range of detectable strains and stresses at both microscopic and nanoscopic length scales. A photonic colloidal array and chemical mechanophore, spiropyran, endow this material with dual mechanoresponsivity for sensitive mechano‐imaging around defects and upon membrane indentation.